2016
DOI: 10.1017/alj.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative model for web archiving ephemeral art resources at the New York Art Resources Consortium (NYARC)

Abstract: The vast expanse and volatility of art ephemera based on the World Wide Web pose significant threats to the completeness of the art historical record. Towards its mission to enhance the resources available for current and future research through collaboration, the New York Art Resources Consortium (NYARC) collects, preserves, and provides access to art ephemera born in digital formats native to the web. It leverages its member institutions’ collecting strengths and resources to establish a permanently sustaina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Also, many other studies focused on the use of technology to manage IK, such as digitisation of IKS (e.g., Bishop, 2019; Bourget, 2020; Kapepiso, 2018; Durcan, 2016; Nakarta et al, 2014); digital preservation of IK (e.g., Amunkete, 2020; Zuraidah and Aliza, 2010; Mutula, 2014; Biyela, Oyelude and Haumba 2016); and web archiving initiatives in academic institutions (Bailey et al, 2017; Hendry and Stock, 2014; Khumalo and Nkala, 2015; Niu, 2012). Very few studies were found on the digital preservation of IKS in Africa.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, many other studies focused on the use of technology to manage IK, such as digitisation of IKS (e.g., Bishop, 2019; Bourget, 2020; Kapepiso, 2018; Durcan, 2016; Nakarta et al, 2014); digital preservation of IK (e.g., Amunkete, 2020; Zuraidah and Aliza, 2010; Mutula, 2014; Biyela, Oyelude and Haumba 2016); and web archiving initiatives in academic institutions (Bailey et al, 2017; Hendry and Stock, 2014; Khumalo and Nkala, 2015; Niu, 2012). Very few studies were found on the digital preservation of IKS in Africa.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The collaborative effort between Drexel University, Slippery Rock University, and the University of Scranton is also a good example of how academic institutions have been able to embark on successful Web archiving initiatives through collaboration (Antracoli et al, 2014). The New York Art Consortium (NYARC) is also able to collaborate to collect, preserve and provide access to “art ephemera born in digital formats native to the web” Duncan and Blumenthal (2016: 116).…”
Section: Web Archiving Policymentioning
confidence: 99%
“…The need for tools that allow seed lists (lists of URLs to archive) to be developed was articulated by Pearce-Moses & Kaczmarek (2005). Duncan & Blumenthal (2016) describe how networks, such as professional consortia, are useful resources for curating seed lists. In addition there has been discussion of the use of social media and their Application Programming Interfaces (APIs) as a means for discovering web content for archiving events such the Arab Spring (Arnold & Sampson, 2014) and the protests in Ferguson and the #Black-LivesMatter social movement (Rollason-Cass & Reed, 2015).…”
Section: Archival Studiesmentioning
confidence: 99%